2014
DOI: 10.3340/jkns.2014.56.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Outcome of Chordoid Meningiomas in a Single Institute

Abstract: ObjectiveMeningioma is the second most common primary central nervous system neoplasm. In contrast, chordoid meningioma is rare; due to the paucity of cases, little is known about its clinical features or treatment outcomes. The objectives of this study were to describe the clinical characteristics and outcomes for patients with chordoid meningioma.MethodsIn total, 16 patients, with newly diagnosed chordoid meningioma who underwent surgical excision between 1999 and 2012 were included. We retrospectively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…[9] Recently, Jee et al reported a mean MIB in 11.56% in 16 patients, ranging from 1-26.6%, without correlation to clinical outcomes. [12] Our data reflect the high variability reported in literature, with a mean MIB-LI of 4.4 and a wide range of 0.1-26.6%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[9] Recently, Jee et al reported a mean MIB in 11.56% in 16 patients, ranging from 1-26.6%, without correlation to clinical outcomes. [12] Our data reflect the high variability reported in literature, with a mean MIB-LI of 4.4 and a wide range of 0.1-26.6%.…”
Section: Discussionsupporting
confidence: 88%
“…Higher MIB-LI has been noted to correlate with recurrent meningiomas [28-30], and has also been correlated with increasing WHO grade, with up to 1.35% for benign, up to 9.3% for atypical and up to 19.5% for anaplastic meningiomas. [12, 29, 31, 32] Despite this established trend, MIB-LI for CMs in the literature have been controversial for 2 reasons: reported ranges of MIB-LI are highly variable within studies, and a lack of correlation with outcomes. Couce et al reported a mean MIB-LI of 5.2% with a range of 0.4-11.4%.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 10 cases of tuberculum sellae CM have been reported in the English literature. [3][4][5][6][7] We describe here a very rare case of tuberculum sellae CM, which was surgically treated via an endonasal approach using a neuro-endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) To date, only a few cases of CM presenting in the tuberculum sellae region have been reported. [3][4][5][6][7]…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis includes chordomas, myxoid chondrosarcoma and chordoid glioma. 1 In the present study, we report a case of a female patient with a diagnosis of a recent onset of headache and visual cloudiness. Meningiomas represent almost 30% of primary intracranial neoplasms.…”
Section: Introductionmentioning
confidence: 92%